2020
DOI: 10.3390/agronomy10020180
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Quantitative Trait Loci for Grain Number in Rice (Oryza sativa L.)

Abstract: Grains number is one of the most important agronomic traits in the determination of rice productivity. To explore the underlying genetic basis of grain number in rice, quantitative trait locus (QTL) analysis was performed using three recombinant inbred line populations derived from indica rice crosses of Teqing/IRBB lines, Zhenshan 97/Milyang 46, and Xieqingzao/Milyang 46, respectively. A total of 58 QTLs distributed on all 12 rice chromosomes were identified, including 22 for number of grains per panicle (NGP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
2
10
1
Order By: Relevance
“…While six SNPs (S1B_547524267, S1B_561712520, S1B_561712544, S2B_28097761, SUN_12527313 and SUN_12527317) were considered a minor QTL with R 2 less than 10%. Many earlier studies reported that large-effect QTLs controlling target trait have R 2 of >10% (Hussain et al, 2017;Mourad A. M. I. et al, 2018;Alqudaha et al, 2019;Mourad et al, 2019;Niu et al, 2020). Kumar et al)2020) detected 349 SNPs associated with stem rust resistance at seedling stage with R 2 ranging from 3.04 to 7.47% which was lower range than reported in this study.…”
Section: Genome-association Study For Stem Rust Resistancecontrasting
confidence: 65%
“…While six SNPs (S1B_547524267, S1B_561712520, S1B_561712544, S2B_28097761, SUN_12527313 and SUN_12527317) were considered a minor QTL with R 2 less than 10%. Many earlier studies reported that large-effect QTLs controlling target trait have R 2 of >10% (Hussain et al, 2017;Mourad A. M. I. et al, 2018;Alqudaha et al, 2019;Mourad et al, 2019;Niu et al, 2020). Kumar et al)2020) detected 349 SNPs associated with stem rust resistance at seedling stage with R 2 ranging from 3.04 to 7.47% which was lower range than reported in this study.…”
Section: Genome-association Study For Stem Rust Resistancecontrasting
confidence: 65%
“…The ve stable SNPs located on two chromosomes (2A and 4A) with R 2 greater than 10% indicating that all the ve signi cant SNPs are controlling major QTLs for stripe rust resistance in the studied materials. All QTLs that explain more than 10% of the total variation is considered major QTLs [23,38].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 200 fully filled grains were selected by 3.5 mol/L NaCl solution. TGW, GL and GW were measured by the methods of Zhang et al 32 .…”
Section: Methodsmentioning
confidence: 99%
“…This type of NIL-F 2 population has been used in cloning many QTLs 7 , 19 , 28 , 31 . NIL-F 2 populations generated by self-pollinating residual heterozygotes (RH) in the recombinant inbred line (RIL) population have validated and dissected many QTLs for grain size and weight 32 34 .…”
mentioning
confidence: 99%